Selective and “Veiled” Demarketing from the Perspective of Black Female Consumers - Rocha, Ana Raquel Coelho; Casotti, Leticia Moreira (Organizações & Sociedade, 2018)
This study sheds light on the perspective of Black female consumers in regards to certain effects of marketing initiatives adopting the literature on demarketing as a framework. The context examined is their experience with the market of hair beauty and care. Media actions are analyzed along narrative interviews in order to understand the phenomenon. The findings reveal a structural dominant pattern which perpetuates the marginalized status of Black women’s natural traits. Emerging market initiatives point to movements concerning the visibility of such female consumers, who despite being eager to consume, have their demand discouraged. This suggests that they perceive a selective and veiled demarketing, as one of the results of marketing actions. The analysis invites for theoretical reflections on demarketing and veiled racism in Brazil.